Combination of cisplatin and lurbinectedin as palliative chemotherapy in progressive malignant pleural mesothelioma: Report of two cases. (December 2016) - Metaxas, Yannis; Cathomas, Richard; Mark, Michael; von Moos, Roger
Highlights: Most malignant mesotheliomas are not curable despite multimodal treatment. Treatment with cisplatin and the novel compound lurbinectedin seems promising. The course of two cases is presented. Abstract: Malignant mesothelioma is an aggressive disease with dismal prognosis despite multimodal treatment including chemotherapy, surgery and radiotherapy. At progression it is possible to provide systemic second-line treatment but its effects are limited. Herein we report two patient cases with mesothelioma who received second-line chemotherapy with the combination of cisplatin and the novel compound lurbinectedin. The combination showed promising activity in both cases with manageable toxicity. We discuss the results of this regime in the light of historical as well as emerging data in mesothelioma.